The treasure of the lost lagoon - Hayes, Geoffrey (New York : Random House, 1991)
Ducky Doodle realizes the true value of his friends Otto and Uncle Tooth when Sid Rat tries to cheat him.
8 13 15 17 19 29
Keywords: Animals -- Fiction; Friendship -- Fiction